THU0067 THREE-MONTH RADIOLOGICAL CHANGES IN WRIST JOINT MEASURED BY MRI AND HR-PQCT CAN PREDICT 12-MONTH CHANGES IN EROSION AND FUNCTIONAL OUTCOMES AFTER MTX AND ANTI-TNF TREATMENT IN PATIENTS WITH RHEUMATOID ARTHRITIS: A MULTI-MODALITY IMAGING STUDY. (June 2019) - Mamoto, Kenji; Shimizu, Tomohiro; Tanaka, Matthew; Pedoia, Valentina; Burghardt, Andrew; Heilmeier, Ursula; Link, Thomas; Graf, Jonathan; Imboden, John; Xiaojuan, LI
Abstract : Background: Magnetic resonance imaging (MRI) provides noninvasive methods to quantify joint inflammation and early cartilage degeneration in monitoring rheumatoid arthritis (RA) progression 1 . High-resolution peripheral quantitative computed tomography (HR-pQCT) provides reliable evaluation of bone erosion volumes 2 . Objectives: To investigate if changes in MR measures from baseline to 3-month (3M) can predict changes in erosion volumes, clinical and functional assessment from baseline to 12-month (12M) in RA patients receiving methotrexate (MTX) and anti-tumor necrosis factor alpha (Anti-TNFα) therapy using MRI and HR-pQCT. Methods: Seventeen RA patients with MTX treatment were recruited into either a low disease activity score (DAS) group (n=9, DAS28≤3.2) or high DAS group (n=8, DAS28>3.2). The low DAS group received MTX treatment only, while the high DAS group received additional Anti-TNFα treatment to MTX immediately after baseline visit (BL). Volumes of synovitis (SYN), bone marrow edema-like lesions (BMEL) and cartilage T1ρ values in wrist joint by MRI, bone erosion volumes in wrist joint by HR-pQCT, DAS28-CRP, Health Assessment Questionnaire (HAQ), and Michigan Hand Outcome Questionnaire (MHQ) were assessed at BL, 3M and 12M in all patients. Longitudinal changes were evaluated using paired t-test. Linear regression models were used to evaluate whether changes in imaging measure changes from BL to 3M predict changes in erosion volumes and patient outcomes (DAS28-CRP, HAQ, MHQ) from BL to 12M, after adjusting for age, gender, disease duration and therapy (Anti-TNFα added or not). Results: Anti-TNFα therapy in the high DAS group resulted in significant decreases of SYN, BMEL at 3M and DAS28-CRP, HAQ and MHQ at 3M and 12M from BL (Table.1 ). The low DAS group in contrast, displayed significant increases in SYN and DAS-CRP at 3M and bone erosion volume at 3M and 12M from BL despite low disease activity (Table.1 ). Changes in SYN, not BMEL, T1ρ or bone erosion, from BL to 3M were significantly correlated with changes in HAQ and MHQ from BL to 12M (P < 0.05), and with changes in DAS-CRP from BL to12 M with marginal significance (P=0.053) (Figure 1 ). Changes in erosion volumes from BL to 3M were significantly correlated with changes from BL to 12M (Figure 1 ). Conclusion: Despite the low disease activity, patients on MTX only showed significantly increased erosion volumes as measured by HR-pQCT at 3M and 12M; on the other hand, patients with MTX+Anti-TNFα treatment showed decreased erosion volumes at 3M and 12M, implying erosion repair. In this study, changes in erosion (but not other MR measures including synovitis and bone marrow edema) within the first 3M predicted changes in erosion at 12M. On the other hand, changes in synovitis volumes predicted patient functional outcomes at 12M. These results suggest that multimodality quantitative imaging with MRI and HR-pQCT provides powerful tools for evaluating early changes and predicting disease progression and therapy response after treatment in RA. Large scale studies with larger sample size are warrant to confirm the observations. References: [1] Shimizu, et al. ACR (2017) [2] Shimizu, et al. Arthritis Research & Therapy (2017) Disclosure of Interests: None declared